A Proposed Management System for Construction Practices during Sustainable Buildings Life Cycle (Journal of Engineering, 2014)
For many years, the construction industry damages have been overlooked such as unreasonable consumption of resources in addition to producing a lot of construction waste but with global awareness growth towards the sustainable development issues, the sustainable construction practices have been adopted, taking into account the environment and human safety. The research aims to propose a management system for construction practices which could be adopted during constructing different types of sustainable buildings besides formulating flowcharts which clarify the required whole phases of sustainable buildings life cycle. The research includes two parts: theoretical part which generally ,handles the sustainability concepts at construction industry and specially buildings .But the practical part comprises investigating the professional opinions in construction industry about applications possibility of sustainable requirements and global criteria to construction of sustainable buildings in Iraq where the weakness and strength points in the essential requirements for achieving the sustainable construction practices have been diagnosed and the development needhas been specified. The utilized statistical analysis of questionnaire results show readiness of buildings sectors to implement the sustainable practices. The different strategies and techniques in the proposed management have been employed for getting the sustainable procedures of sequences practices within project life cycle.